Pemberian Biochar Arang Kayu dan Tandan Kosong Sawit terhadap Gas N2O pada Tanah Gambut yang Ditumbuhi Kelapa Sawit - Anita Dewi Astanti; Abdul Hadi; Hairil Ifansyah (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2024)
Peatlands are developed for agricultural cultivation, such as oil palm. The agricultural sector contributes 13.5% of the total greenhouse gas (GHG) emissions. Emissions from this sector are generally in the form of N2O 46%, CH4 45%, and CO2 9%. Recently, the focus on the development of peatlands for this activity has been so great, especially in relation to emissions of nitrous oxide (N2O). The potential for peatland to be used as agricultural land must pay attention to environmental aspects such as the level of N2O emissions. This study aims to determine the effect of wood activated to empty palm oil fruit bunches on N2O emissions from peatlands oil palm. This study used an allocation block design. The factors studied were the distribution of wood charcoal and empty palm oil bunches at 6 levels, namely: wood charcoal + 0 kg of empty palm fruit bunches; wood charcoal 0.75 kg + 0.75 kg of empty palm fruit bunches, and 0.375 empty palm fruit bunches+0.375 kg of wood charcoal; empty palm fruit bunch charcoal 1.5 kg+wood charcoal 1.5 kg. N2O gas was analyzed using the closed chamber method and the soil was analyzed for soil pH and field water capacity. The treatment was repeated 3 times, resulting in 18 experimental units. The results showed that on day 0, the application of wood charcoal and empty palm oil bunches did not affect N2O emissions, but on the 15 and 45 days. The results showed that the treatment affected N2O emissions.